1979
DOI: 10.1139/f79-134
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake and Nutritional Characteristics in Wild American Lobsters (Homarus americanus)

Abstract: Nutrient and essential amino acid analyses of the stomach contents of wild adult American lobsters (Homarus americanus) collected from offshore and inshore populations indicated lobsters consumed varying nutrient levels according to their stage of molt. For example, soft-shell lobsters ate a higher level of mineral constituent. The location of the animal had no effect on the level of nutrient intake. The essential amino acid composition of the protein in the stomach remained the same throughout the molt cycle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The observed pH of the gastric fluid was 4.8 and approximated the pH reported by Brokerhoff et al (1970), Hoyle (1973) and Leavitt (1977). Gastric fluid pH was 4.8 before and after experiments at full strength and when diluted 1:1 with artificial seawater.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The observed pH of the gastric fluid was 4.8 and approximated the pH reported by Brokerhoff et al (1970), Hoyle (1973) and Leavitt (1977). Gastric fluid pH was 4.8 before and after experiments at full strength and when diluted 1:1 with artificial seawater.…”
Section: Resultssupporting
confidence: 80%
“…homari (formerly Gaffkya homari) (Kelly and Evans 1974), of lobsters is killed by gastric fluid (Stewart et al 1969). The acidity of the lobster gastric fluid is mild, centering around a pH of 5.0 (Brokerhoff et al 1970;Hoyle 1973;Leavitt 1977), and survival under these conditions is possible.…”
Section: Introductionmentioning
confidence: 99%
“…The digestive gland plays a primary role in moulting and oogenesis in Nephrops (Dall 1981), and in Panulirus argus it has been shown to be important for both chitin synthesis and calcium storage during moulting (Tsokos et al 1983). Homarus amencanus has specific dietary requirements prior to moulting (Leavitt et al 1979). If these requirements are not met, moulting may be delayed (Castell & Budson 1974, Castell & Covey 1976 but can still take place, even though the lobster is physiologically incapable of moulting and subsequently dies (Bayer et al 1978).…”
Section: Discussionmentioning
confidence: 99%
“…data). Lobsters suffer an increased vulnerability during their molting period as well as demonstrating molt-related shifts in diet (Ennis 1973, Leavitt et al 1979, Scarratt 1980. Lobster remains have also been encountered in lobster stomachs in other studies (Weiss 1970, Carter & Steele 1982; although we determined that some remains could have been from cast exuviae, others, associated with flesh, indicated that cannibalism was occurring.…”
Section: Discussionmentioning
confidence: 99%